Fortifying learners’ self-regulation in biology through career-oriented teaching - Honra, Joelash R.; Monterola, Sheryl Lyn C.; T. Yangco, Rosanelia (International Journal of Evaluation and Research in Education (IJERE), 2024)
Incorporating career-oriented teaching (COT) in technical-vocational education addresses challenges in graduates’ job readiness by emphasizing practical skills aligned with career interests. This study investigates the impact of COT on students’ self-regulation in biology, which is crucial for academic and career success. Quantitative analysis reveals that COT significantly enhances self-regulation skills, including decision-making, goal orientation, impulse control, and self-direction, compared to conventional science teaching (CST). Qualitative responses underscore the positive influence of COT on decision-making and goal orientation, with students setting positive goals and exhibiting improved impulse control. Moreover, COT fosters self-direction, promoting autonomy and responsibility for learning. These findings emphasize the importance of innovative teaching approaches like COT in developing students’ self-regulation abilities and preparing them for the demands of the modern workforce. Integrating concrete, problem-based tasks in COT and teacher training can further enhance its effectiveness in developing specialized skills and self-regulation. This research contributes valuable insights into instructional practices’ role in shaping students’ self-regulation and highlights the need to explore further innovative teaching strategies to support students’ holistic development.